Effects of host restriction factors and the HTLV-1 subtype on susceptibility to HTLV-1-associated myelopathy/tropical spastic paraparesis - Nozuma, Satoshi; Matsuura, Eiji; Kodama, Daisuke; Tashiro, Yuichi; Matsuzaki, Toshio; Kubota, Ryuji; Izumo, Shuji; Takashima, Hiroshi (Retrovirology, 2017)
Although human T-lymphotropic virus type 1 (HTLV-1) infection is a prerequisite for the development of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), specific provirus mutations in HAM/TSP have not yet been reported. In this study, we examined whether HAM/TSP patients had the disease-specific genomic variants of HTLV-1 by analyzing entire sequences of HTLV-1 proviruses in these patients, including familial cases. In addition, we investigated the genetic variants of host restriction factors conferring antiretroviral activity to determine which mutations may be related to resistance or susceptibility to HAM/TSP. The subjects included 30 patients with familial HAM/TSP (f-HAM/TSP), 92 patients with sporadic HAM/TSP (s-HAM/TSP), and 89 asymptomatic HTLV-1 carriers (ACs). In all 211 samples, 37 samples (18%) were classified into transcontinental subtype and 174 samples (82%) were classified as Japanese subtype. Among three groups, the percentage of transcontinental subtype in f-HAM/TSP, s-HAM/TSP and ACs was 33, 23 and 7%, respectively. The frequency of transcontinental subtype was significantly higher in both f-HAM/TSP (p < 0.001) and s-HAM/TSP (p < 0.001) than in ACs. Fifty mutations in HTLV-1 sequences were significantly more frequent in HAM/TSP patients than in ACs, however, they were common only in transcontinental subtype. Among these mutations, ten common mutations causing amino acid changes in the HTLV-1 sequences were specific to the transcontinental subtype. We examined host restriction factors, and detected a rare variant in TRIM5α in HAM/TSP patients. The patients with TRIM5α 136Q showed lower proviral loads (PVLs) than those with 136R (354 vs. 654 copies/10 PBMC, p = 0.003). The patients with the 304L variant of TRIM5α had significantly higher PVLs than those with 304H (1669 vs. 595 copies/10 PBMC, p = 0.025). We could not find any HAM/TSP-specific mutations of host restriction factors. Transcontinental subtype is susceptible to HAM/TSP, especially in familial cases. Ten common mutations causing amino acid changes in the HTLV-1 gene were specific to the transcontinental subtype. TRIM5α polymorphisms were associated with PVLs, indicating that TRIM5α could be implicated in HTLV-1 replication.